Aóyoc and oúcría in the Plato’s Sofist - Escobar Moncada, Jairo (Estudios de Filosofía, 1998)
This essay discusses the relation betwen language and being, and how Plato conceives it. First, critiques that Plato makes to precedent ontological theories are reconstructed as well as the famous gigantomachy around being. All of them have a common aspect: they do not know the fundamental role of Lagos in knowing the being. Then, image function in the knowledge is discussed and what is the relation between language and image. Finally, it asks if the word lagos has to be understood as sentence in the last part of the dialogue or it has a different meaning.